On forced vibration of shrouded turbine blades - Szwedowicz, J; Sextro, Walter; Visser, R; Masserey, P.A (ASME Turbo Expo 2003, collocated with the 2003 International Joint Power Generation Conference)
Numerical predictions of the forced vibration of a disc assembly including frictional effects between the shrouds are presented concerning engineering needs for the blade design process. Assuming a tuned disc assembly, numerical static, free and then forced vibration analyses of a shrouded turbine blade measured in the spin pit are performed systematically. For the excitation forces of an air jet evaluated from the fairly linear behavior of the experimental blade resonance peaks, the reliability of the proposed approach is validated through the very close agreement of the computed and measured resonant peaks. These resonant peaks demonstrate either a fairly linear behavior or a non-linear one like the jump effect of blade resonance amplitudes, or elastic impacts between the shrouds. Also, the damping performance for different contact configurations between the shrouds is numerically analyzed. These numerical results indicate that the shrouds generate higher frictional damping for small angles (0--30 deg) between the circumferential direction and the normal vector to the contact surface. Copyright {©} 2003 by ASME
Keywords: Turbine blades; Vibration